Assessment of Jerusalem artichoke as a source for the production of gluten-free flour and fructan concentrate by ultrafiltration - M.V. Ostermann-Porcel; A.N. Rinaldoni; M.E. Campderrós (Applied Food Research, 2022)
Jerusalem artichoke (JA) is a tuber considered a functional food. The tubers accumulate a high amount of fructans (inulin and fructo-oligosaccharides) although tubers also have a high content of minerals and proteins of high biological value. In this study Jerusalem artichoke flour (JAF) was obtained by means of two drying methodologies: convective air oven drying and freeze-drying. Physico-chemical characteristics were analyzed in both samples, as well as a colorimetric analysis and microstructure. As a by-product of the production of JAF, a residual liquid is obtained from which fructans can be extracted, this process included separation steps in aqueous medium without the addition of organic solvents. The optimal extraction conditions were: solid/solvent ratio of 1:2 (Kg JA / L distilled water) during 40 min at 90 ± 5 °C. The flours obtained presented a high protein and fiber content, 9.73–9.94% and 1.21–1.47% respectively, while the morphology of the matrix of protein and inulin could be observed by microscopy. These results allow them to be considered as an alternative raw material for the production of gluten-free products in order to overcome the nutritional deficiency that gluten-free products generally have. The fructans extraction yield was affected by the temperature and storage time of the tubers. The concentration of fructans was performed by ultrafiltration, the process was stopped when the desired volume concentration ratio was achieved (VCR = 3.24). The concentrate stream was lyophilized. The results showed the following centesimal compositions: 6.65% proteins; 0.22% fat; 7.50% ash; 6.60% moisture and 4% inulin. The use of JA tubers allowed to obtain a gluten-free alternative flour with good nutritional characteristics. Therefore, JA tubers present a high potential for the production of inulin through chemical-free methods, from the by-product of the JAF process.